2021
DOI: 10.1088/1755-1315/657/1/012034
|View full text |Cite
|
Sign up to set email alerts
|

Study on the removal of hydrogen sulfide from natural gas by titanosilicite zeolite

Abstract: The presence of hydrogen sulfide in natural gas will reduce the calorific value of natural gas, so hydrogen sulfide in natural gas needs to be removed. Titanosilicalite zeolite is a stable porous material with good catalytic effect and has attracted much attention due to its excellent catalytic oxidation performance in the system composed of it and hydrogen peroxide. Therefore, in this paper, the removal of hydrogen sulfide in natural gas was studied by using titanosilicalite zeolite as catalyst and hydrogen p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Bowen et al [55] investigated hydrogen sulfide removal from natural gas using titanosilicite zeolite (TS-1) in the presence of hydrogen peroxide and examined the effect of reaction temperature and H 2 O 2 concentration on the catalytic oxidation. The result showed that increasing the reaction temperature and H 2 O 2 concentration increase the catalytic oxidation of TS-1 towards H 2 S. In Table 5, studies based on modification of synthetic zeolites are summarized.…”
Section: Synthetic Zeolites and Their Modificationsmentioning
confidence: 99%
“…Bowen et al [55] investigated hydrogen sulfide removal from natural gas using titanosilicite zeolite (TS-1) in the presence of hydrogen peroxide and examined the effect of reaction temperature and H 2 O 2 concentration on the catalytic oxidation. The result showed that increasing the reaction temperature and H 2 O 2 concentration increase the catalytic oxidation of TS-1 towards H 2 S. In Table 5, studies based on modification of synthetic zeolites are summarized.…”
Section: Synthetic Zeolites and Their Modificationsmentioning
confidence: 99%